Tipe dan Usabilitas Website dalam Konteks Manajemen Informasi - Novianni Anggraini (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2021)
This study is aimed to analyze type design and also the usabilty of the website in Madrasah Aliyah Kejuruan Unggulan Informatika Jakarta website. The method of research used in this study is content analysis. the way data gained from obsrvation and queesionnaire. The result of the study shows that type of website used in Madrasah Aliyah Kejuruan Unggulan Informatika Jakarta is dynamic using domain sch.id, and the usability of the website is good as one of the system information used in this madrasah.